2015
DOI: 10.2147/tcrm.s68752
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic assessment of left ventricular function in thyrotoxicosis and implications for the therapeutics of thyrotoxic cardiac disease

Abstract: IntroductionThyrotoxicosis is an endocrine disorder with prominent cardiovascular manifestations. Thyroid hormone acts through genomic and non-genomic mechanisms to regulate cardiac function. Echocardiography is a useful, non-invasive, easily accessible, and affordable tool for studying the structural and physiological function of the heart.AimWe studied thyrotoxicosis patients in a Nigerian Teaching Hospital and employed trans-thoracic echocardiography to find out if there were abnormalities in the hearts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 60 publications
7
21
2
1
Order By: Relevance
“…A higher prevalence of 72% and 100% is found by Tsymbaliuk et al [13] in Ukraine and Diallo et al [7] in Mali respectively. In contrast to clinical finding which are suggestive of right heart involvement [7], electrocardiographic findings are more indicative of left heart involvement [15]. In a comparative prospective study between two Senegalese populations with and without cardiothyreosis, Kane et al [14] reported a significantly higher left ventricular mass in population with thyrotoxic heart disease.…”
Section: Electrocardiographic and Echocardiographic Study Of Cardiothmentioning
confidence: 97%
“…A higher prevalence of 72% and 100% is found by Tsymbaliuk et al [13] in Ukraine and Diallo et al [7] in Mali respectively. In contrast to clinical finding which are suggestive of right heart involvement [7], electrocardiographic findings are more indicative of left heart involvement [15]. In a comparative prospective study between two Senegalese populations with and without cardiothyreosis, Kane et al [14] reported a significantly higher left ventricular mass in population with thyrotoxic heart disease.…”
Section: Electrocardiographic and Echocardiographic Study Of Cardiothmentioning
confidence: 97%
“…However, in this study only in 20% of cases was the hypertension systolic suggesting pre-existing diastolic hypertension. The large burden of cardiac disease seen in thyrotoxicosis in Africa has been noted by several authors , Anakwue et al 2015. This was attributed to some genetic susceptibility.…”
Section: Thyrotoxicosis Hypertension and Heart Diseasementioning
confidence: 87%
“…Hyperthyroidism is defined as a clinical condition that resulted from abnormal high serum thyroid hormone levels [ 1 ]. Any increase in the level of thyroid hormone leads to change in many systems of human body including cardiovascular system because thyroid hormone acts through genomic and non-genomic mechanisms to regulate cardiac function [ 2 ]. Cardiomyocytes have thyroid hormone nuclear receptors that when bound alter gene transcription, can regulate intracellular calcium metabolism and myofilaments.…”
Section: Introductionmentioning
confidence: 99%